Inbound Call Centers and Emotional Dissonance in the Job Demands – Resources Model - Molino, Monica; Emanuel, Federica; Zito, Margherita; Ghislieri, Chiara; Colombo, Lara; Cortese, Claudio G. (Frontiers in Psychology, 2016)
Background: Emotional labor, defined as the process of regulating feelings and expressions as part of the work role, is a major characteristic in call centers. In particular, interacting with customers, agents are required to show certain emotions that are considered acceptable by the organization, even though these emotions may be different from their true feelings. This kind of experience is defined as emotional dissonance and represents a feature of the job especially for call center inbound activities. Aim: The present study was aimed at investigating whether emotional dissonance mediates the relationship between job demands (workload and customer verbal aggression) and job resources (supervisor support, colleague support and job autonomy) on the one hand, and, on the other, affective discomfort, using the job demands-resources model as a framework. The study also observed differences between two different types of inbound activities: customer assistance service and information service. Method: The study involved agents of an Italian Telecommunication Company, 352 of whom worked in the customer assistance service and 179 in the information service. The hypothesized model was tested across the two groups through multi-group structural equation modeling. Results: Analyses showed that customer assistance service agents experience greater customer verbal aggression and emotional dissonance than information service agents. Results also showed, only for the customer assistance service group, a full mediation of emotional dissonance between workload and affective discomfort, and a partial mediation of customer verbal aggression and job autonomy, and affective discomfort. Conclusion: This study’s findings contributed both to the emotional labor literature, investigating the mediational role of emotional dissonance in the job demands-resources model, and to call center literature, considering differences between two specific kinds of inbound activities. Suggestions for organizations and practitioners emerged in order to identify practical implications useful both to support employees in coping with emotional labor and to promote well-being in inbound call centers. In detail, results showed the need to improve training programs in order to enhance employees’ emotion regulation skills, and to introduce human resource practices aimed at clarifying emotional requirements of the job.